Experimente o vento: métodos e conceitos para a construção de uma experiência esportiva única e memorável na modalidade vela - Santiago, Daniel Rabha Nunes (2022)
Creative economy contributes to the development of business models structured from concepts such as experience economy, innovation of meaning, and sharing economy. These models facilitate people's access, raise value of goods and services, and sustain the progress of regions, cities, and countries. Offering an experience using sailing as main attraction has the potential to promote health, quality of life, and full development of practitioners. However, limitations inherent to the activity, linked to sports equipment and place of practice, must be considered. That said, this study aims to define contributing elements to design sports experience that encourages the practice of sailing in the city of Rio de Janeiro, for leisure, entertainment, and personal development. To this end, it is necessary to examine concepts that may be applied to the practice of sports, as a way to encourage new practitioners, point out possibility conditions of the city linked to its technical, social and institutional networks, as well as analyze how business models focused on sharing of goods and digital platforms can contribute to the construction of such experience. In the first stage, a bibliographical and documental research is carried out on the pertinent themes. Next is field research, divided into three phases. Phase one was aimed at collecting data from entrepreneurs who offer outdoor sports experiences, and phase two, under the same methodological pattern, had as its target audience frequent practitioners of outdoor sports activities. Both by means of qualitative research, conducting in-depth interviews with a semi-structured script. Finally, phase three was carried out through quantitative research, upon application of a closed questionnaire to practitioners of outdoor physical activities in the city. Given the foregoing, the application of theories such as flow experience or state of optimal experience can help in the search for a differential that encourages practice of the sport and makes it stand out from the others. Furthermore, the shared supply of sports equipment and use of adequate public spaces present themselves as determining factors to expand access to the sport in question. The application of the concepts, allied to the results presented, facilitates the creation of a unique, authentic experience that brings meaning to those involved, beyond the practice of sports